A dual-process team mood framework of team creativity - LEE, Sean Teck Hao (Institutional Knowledge at Singapore Management University, 2018)
While it has been recognized that mood can exert a substantive influence on an individual’s level of creativity, much of the creative needs of organizations today are being fulfilled by brainstorming teams rather than individual employees. As such, researchers have begun to examine the effects of mood on creativity in the context of teams. Existing findings, unfortunately, have not been consistent, such that positive mood has been shown to be beneficial towards team creativity at times (e.g., Grawitch, Munz, Elliott, & Mathis, 2003), while at other times being harmful towards team creativity (e.g., Tsai, Chi, Grandey, & Fung, 2012). Similarly, negative mood has also been shown to benefit team creativity at times (e.g., Jones & Kelly, 2009), while harming team creativity at other times (e.g., Klep, Wisse, & Van der Flier, 2011). To better understand and reconcile such discrepancies, we constructed a dual-process team mood framework by considering past findings pertaining to the team mood-team creativity relationship in relation to the dual team information processing pathways of team creativity (i.e., team generative processing and team information elaboration). Within this framework, we proposed that both positive team mood and negative team mood can lead to increased team creativity, albeit via different means. Specifically, we postulated that positive team mood heightens novelty of ideas generated by facilitating team generative processing, whilst negative team mood heightens novelty of ideas generated by facilitating team information elaboration. Additionally, we postulated that team generative processing increases fluency of ideas (i.e., greater quantity of ideas) while team information elaboration improves the practicality of ideas generated. An experimental study was conducted on 105 teams (378 participants) to test our proposed dual-process team mood framework of team creativity, where teams were randomly assigned to either a positive, negative, or neutral mood condition. The relevant team moods were experimentally induced via a combination of the established musical mood induction procedure and the Velten mood induction procedure (see Albersnagel, 1988). As hypothesized, teams under a positive mood were found to exhibit increased engagement in team generative processing, which consequently led to increased fluency of ideas and novelty of ideas generated. However, contrary to our hypothesis, teams under a negative mood were not found to exhibit increased engagement in team information elaboration, even though team information elaboration levels were found to predict increased novelty of ideas generated. While only partial support was found for our dual-process framework, we believe that our findings and approach represent a major step forward in elucidating the relationship between team mood and team creativity, which would serve both to inform current interventions and guide future studies in this area.